Task-oriented training and exer-gaming for improving mobility after stroke: a randomized trial - Arshad Nawaz Malik; Tahir Masood (Journal of the Pakistan Medical Association, 2020)
Objective: To evaluate the effects of task-oriented training and to compare it with virtual reality training on the mobility, physical performance and balance in stroke patients. Method: The randomised controlled trial was conducted from January 2016 to March 2017 at the Physical Rehabilitation Department of Pakistan Railways General Hospital, Rawalpindi, Pakistan, and comprised patients 40-70 years with stroke history of at least 3 months who had the ability to stand unaided. The subjects were randomised into virtual reality training group A and task-oriented training group B. Task oriented training was provided for 3 days per week over 8 weeks to both groups with each session lasting 40-45 minutes, while additional 15-20 minutes of exer-gaming was provided only to group A. Fugl-Meyer Assessment-Lower Extremity, Berg Balance Test, Timed Up and Go Test and Dynamic Gait Index were used for assessment which was done at baseline, and at 2, 4, 6 and 8 weeks of training. Data was analysed using SPSS 21. Results: Of the 52 subjects, there were 26(50%) in each of the two groups. The overall sample had 36(69.2%) males and 16(30.7%) females. Group A showed significant difference in Fugl-Meyer Assessment-Lower Extremity and Berg Balance Test scores at 04 weeks of training compared to group B (p<0.05). Timed Up and Go Test significantly improved in group A at 6 weeks (p<0.05). Both groups showed significant improvement in Dynamic Gait Index after 8 weeks of training (p>0.05). Continuous....